Desain Irigasi Tetes Bawah Permukaan Berdasarkan Konduktivitas Hidraulik Tanah untuk Tanaman Hortikultura - Muhammad Idrus; Erie Maulana (Jurusan Teknologi Pertanian, 2014)
Subsurface drip irrigation is designed base on the soil hydraulic conductivity in order to water drip out from emitter not overflow to soil surface so that application of water irrigation more efficent. The objectives of the research were (1) To compose matematic equation for determining diameter of hole emitter sub surface drip irrigation base on soil hydraulic conductivity so that emitter discharge not more than soil hydraulic conductivity; (2) To constract the physic model of subsurface drip irrigation conform with the design in this research; (3) To test performances design result of the subsurface drip irrigation at the research station with plant indicator is chilly with 4, 6, 8, and 10 days irrigation interval. The result of the research showed that the diameter of hole emitter of subsurface drip irrigation base on the equation /2.4/ for clay, sandy loam, and sand textures are 3,3; 4,7; and 6,6 mm respectively without water overflow from hole emiter to the soil surface.The irrigation interval of 6 days by using subsurface drip irrigation until day old of chilly 50 days after planting gave production 0,561 kg plant-1 and economical benefit per unit of water. Water productivity of chilly with 6 days irrigation interval is very high of 6.56 kg m-3 of water. Keywords: subsurface drip irrigation, hole diameter emitter, chilly, irrigation interval.